Conceptualizing green infrastructure in cities located in the margin of Kavir - Masoud Ghaderian; Koroush Golkar; Pantea Hakimian (علوم محیطی)
Introduction: Following the discovery, development, and maturation of green infrastructures, researchers have defined them as an integrated network of natural and semi-natural elements, providing a wide range of features and ecosystem services including ecological, economic, and social benefits for humans and other species. Today, green infrastructures are considered a part of novel water management paradigms in urban form and water studies. Regarding the management of water in cities in Iran, particularly those located on the fringe of Dasht-e Kavir, it is necessary to outline the operational definition of green infrastructures as networks in the ecosystem on the fringe of Dasht-e Kavir. Moreover, it is important to explain green infrastructures in arid and semi-arid regions, detailing the features. Accordingly, this study aimed to identify green infrastructures in Iranian desert cities. To achieve this goal, two main steps were specified: 1. Operational investigation and definition of green infrastructures in the mature urban and water discourses and 2. Proving green infrastructures applicable in desert-fringe cities through cases.Material and methods: As the first step was determining the operational definition of green infrastructures, the content of literature related to the development and establishment of the concept of green infrastructures published between 2005 and 2020 was qualitatively analyzed. Consequently, a conceptual framework was developed for the operational definition of green infrastructures. In this study, content analysis used in qualitative studies was selected for examining the literature on environmental design with an inductive approach in order to identify the existing themes in the definition of green infrastructures. This method was selected to systematically analyze, summarize, categorize, and induce the literature including the definition of green infrastructures in order to shed light on the hidden meanings and pave the way for comparison with the infrastructures of historical cities located on the fringe of Dasht-e Kavir. In this study, the stages were in six steps: 1. Stating the problem, 2. Developing questions and aims, 3. Defining and determining variables, 4. Sampling and selecting analysis and background units, 5. Coding and categorizing, and 6. Analyzing, inducing, and reporting.Results and discussion: The results of the qualitative content analysis yielded seven categories as follows: 1. The morphology of green infrastructures is influenced by the systemic nature of urban networks which consist of natural and artificial elements in the form of patches, corridors, and matrices to ultimately connect water and ground. 2. The establishment of macro or microgreen infrastructures, both inside and outside the cities and villages, have an extensive geographic dispersion. 3. Green infrastructures are multi-functional. 4. Green infrastructures develop in natural (animate or inanimate), artificial, and human backgrounds. 5. Green infrastructures create values through economic, social, and physical benefits. 6. Green infrastructures provide ecosystem services. 7. Green infrastructures will ultimately lead to sustainable management of resources.The green infrastructure network is available in the cities located on the fringe of Dasht-e Kavir in Iran as a multi-functional value-creating system for providing ecosystem services and with the aim of sustainable management of resources. In operational terms, from the qanats, gardens, and floodways to urban and architectural spaces all form a multi-functional network of natural components such as gardens and artificial components such as qanats in linear form (corridors), spots, and arena such as the flexible seasonal green network between upstream and downstream hamlets for the two-way connection of water and ground in hot and arid climate. Conclusion: Green infrastructure not only refers to urban organs which are a part of a natural and human-made ecological network but also applies to a scientific approach and method of environmental design and planning in which the best type of connection between water and urban form is available for supporting both natural and artificial processes in the management of water resources in the historical cities located on the fringe of the Dasht-e Kavir in Iran. Even in such hot and arid regions, green infrastructures are available as a multi-functional value-creating system for providing ecosystem services with the aim of sustainable management of resources. This network includes a wide range of natural and human-made water-based elements such as qanats, gardens, floodways, and urban spaces and architecture.